Unveiling the Potential of Friction Stir Welding for Seamless Metal Joining: Mengungkap Potensi Pengelasan Aduk Gesekan untuk Penyambungan Logam Tanpa Batas - Rahmadan, Dicky Fajar; Mulyadi (Indonesian Journal of Innovation Studies, 2024)
Friction Stir Welding (FSW) has revolutionized metal joining in manufacturing by offering robust joints without defects. This study examines FSW using specific parameters and evaluates its impact on mechanical properties and microstructure. Through rotational speed (2192 RPM), welding speed (36.3 mm/minute), tool tilt (3.4°), and concave shoulder angle (9°), FSW was applied to predetermined metal materials. Impact and Vickers tests were conducted post-welding to assess toughness, surface hardness, and microstructural changes. Results highlight the significant influence of FSW parameters on material properties, providing insights for optimizing efficiency and quality in the manufacturing industry. The study's findings contribute to addressing knowledge gaps and advancing FSW applications in industrial settings. Highlight: Precise Parameters: Control for strong joints in manufacturing. Toughness Evaluation: Assessing joint resilience under dynamic loads. Industry Optimization: Enhancing efficiency and quality in metal joining processes. Keywoard: FSW, Manufacturing, Mechanical Properties, Optimization, Impact Testing